Review on the Effects of Process Parameters on Strength, Shrinkage, and Warpage of Injection Molding Plastic Component - Mohan M.; Ansari M.N.M.; Shanks R.A. (Taylor and Francis Inc., 2023)
Molding; Polypropylenes; Shrinkage; Injection molded part; Injection molding process; Injection parameters; Plastic components; Process parameters; Relative stiffness; strength; Warpages; Injection molding